The Adoption of a Standardized Antibiotic Sensitivity Test in the Philippines - Tupasi-Ramos, Thelma (Science Diliman: A Journal of Pure and Applied Sciences; Vol 1 (1980), 2007)
Excerpt With the development and the introduction of a great variety of antibiotic and chemotherapeutic agents, the outlook in the treatment of infections has improved significantly. Unfortunately, however, these agents are not necessarily innocuous to human tissues, so that their use in some instances is associated with some potential hazards including tissue toxicity, hypersensitivity reaction, emergence of bacterial antimicrobial resistance and the development of clinical superinfection. In view of these hazards, therefore, the administration of an antibiotic must be initiated only when there are definite objective evidences of an infection from clinical and laboratory parameters. Furthermore, the choice of antibiotic must be based on objective results of the antibiotic sensitivity test done on the isolated etiologic agent.